The scope of ‘Illah (causal effect) of ribā prohibition on gold and silver: a juristic analysis - Busari, Saheed Abdullahi; Akanbi, Ridwan Ayomide; Abdul Aziz, Akhtarzaitie (UITM Press, 2024)
There is a consensus among Muslim scholars that ribā (usury) is generally forbidden in Islamic law. However, there is a subjective interpretation of the scope and limitations regarding its criteria and sub-rulings. The jurists are unanimous that the prohibition of ribā in Islam is definitive, but the application to different modern currencies is subject to interpretation. Whether the ‘illah (causal effect) of the prohibition of ribā should be limited to gold and silver or extended to other currencies recognized as mediums of exchange. According to a tradition of the Prophet PBUH, that considers exchange of gold, silver, wheat, barley, and dates as ribawī items (usurious) unless the exchange is done hand to hand and in equal amounts. This study aims to explain why the classical jurists of the Shafi’i school of law opined that gold and silver are the main currencies considered mahal al-‘illah (place of causal effect), where ribā is likely to occur. This opinion further stresses that the ‘illah of ribā is limited to gold and silver because they were mainly used as prices in the classical era. However, there is a need to explicate the sociological influence that suggests the position of the classical Shafi’i scholars for limiting the application of the ‘illah to gold and silver specifically, without consideration for non-gold or silver coins as substitute currencies. There is a need for further investigation into the reasons behind non-extension, whether its extension is prohibited in this matter or because there was no available paper currency during the classical time, which made some of the scholars of Shafi’i limit mahal al-‘illah to only gold and silver. The paper uses a doctrinal approach of qualitative methods to analyze the reasons why some classical scholars of Shafi’i positioned that the ‘illah of ribā prohibition is limited to gold and silver, while others contend the permissibility of analogical deduction (qiyās) to extend and interpolate the‘illah of ribā from gold and silver to modern currencies.